2020
DOI: 10.1111/jerd.12680
|View full text |Cite
|
Sign up to set email alerts
|

Interdental papilla reconstruction using injectable hyaluronic acid: A 6 month prospective longitudinal clinical study

Abstract: The objective of this study was to assess the efficacy of Hyaluronic Acid (HA) on interdental papilla (IDP) loss in the esthetic zone. Twenty one subjects (14 females and 7 males) from those referred for treatment of IDP loss at Periodontics postgraduate clinics at the Jordan University of Science and Technology. A total of 86 interdental sites (58 sites in the maxillary jaw and 28 sites in the mandibular jaw) were treated and followed up. A 0.2 ml of Hyaluronic acid was injected in each receded IDP site and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 15 publications
0
26
0
2
Order By: Relevance
“…The greatest weight in this review with the lower variability was shown by Alhabashneh [16] who presented 21 (14 females, 7 males) patients and a total number of treated interdental papillary sites of 86. Overall, there was statistically significant difference in black triangle reduction between maxillary and mandibular sites at 3 and 6 months with more reduction observed in maxillary one.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The greatest weight in this review with the lower variability was shown by Alhabashneh [16] who presented 21 (14 females, 7 males) patients and a total number of treated interdental papillary sites of 86. Overall, there was statistically significant difference in black triangle reduction between maxillary and mandibular sites at 3 and 6 months with more reduction observed in maxillary one.…”
Section: Discussionmentioning
confidence: 86%
“…The greater weight in this review was obtained by the study of Alhabashnaeh [16] with a 39.6%. Even more, it had the lowest dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…The presence or absence of the interdental papilla was and still is a great concern to periodontists and patients (6) .…”
Section: Discussionmentioning
confidence: 99%
“…HA was used to reconstruct interdental papilla in 21 patients. [ 197 ] HA was injected into the interdental papilla loss site and reinjected every 21 d. After 6 months of treatment, the black triangle was significantly reduced. It is worth noting that HA is largely used as skincare products to improve skin health.…”
Section: Application Of Polysaccharide Scaffoldsmentioning
confidence: 99%